The omen machine [compact disc, unabridged] - Goodkind, Terry (Goodkind, Terry. Sword of truth., 2011)
A deep underground machine awakens after thousands of years and foretells ominous events including a catastrophic prediction involving Richard Cypher and Kahlan Amnell.